CLINICAL RESULTS FOR STAGE III·IV CANCER OF THE TONGUE - Mitani, Hiroki; Nigauri, Tomohiko; Yonekawa, Hiroyuki; Kamata, Shin-etsu (JIBI INKOKA TEMBO, 2003)
Our department has been treating patients with tongue cancer since 1946. Until the early 1980 s, treatment for primary lesions consisted mainly of a small dose of radium irradiation, regardless of the clinical stage. The approximate 5-year survival rate for progressive tongue cancer with a staging of greater than T 3 was as low as 20.3% (N =137) between 1946 and 1970. Irradiation methods have since improved, and the resection-reconstruction method using a deltopectral skin flap had been introduced. In addition, a trend has emerged towards performing surgical treatment and reconstructions using a greater pectoral muscle skin flap. As a result, the approximate 5-year survival rate for T 3+ T 4 tongue cancer improved to 37.0% (N =40) for the period between 1971 and 1980. In 1982, a reconstruction technique using a free skin flap with the goal of reconciling the preservation of function and an improvement in the clinical results was established. Treatment protocols have changed drastically since then, making it possible to perform an extended resection while maintaining the swallowing function. As a result, the approximate 5-year survival rate for T 3+ T 4 tongue cancer has improved to 51.6% (N =126). This paper describes the clinical outcome for stage III and IV progressive tongue cancerstreated mainly by surgery over the past twenty years. The subjects included 192 cases of stage III or IV squamous cell carcinoma of the tongue ; all of the subjects underwent radical operations between January 1981 and December 1999. The approximate 5-year survival rate (disease-specific survival rate) for stage III cancers was 65.3% (71.8%) (N=123), while that for stage IV cancers was 38.2% (40.0%) (N =69). The 5-year primary lesion control rate according to T classification was as follows : T 1, 100%, T 2, 83.8%, T 3, 81.7% ; and T 4, 77.4%. The 5-year neck control rate was 77.1%. Our department, in principle, usually administers external irradiation at a dosage of 40 Gy. We histologically reclassified biopsied specimens of primary lesions according to the efficacy of preoperative irradiation and studied the relation between preoperative irradiation and the clinical results. The appearance rate was 40% (53/132) in the group that was an responsive to irradiation and 60% (79/132) in the group that was responsive. The difference in the primary lesion-neck control rates and the approximate survival rates of the two groups was significant (p <0.05). Some cases responded to irradiation treatment even at a dosage of 40 Gy. These results suggest that preoperative irradiation is an effective adjuvant therapy in the treatment of progressive tongue cancer, since there is a limit to the improvement in clinical results that can be obtained by surgical treatment alone.